Pengaruh Layanan Konseling Kelompok Teknik Cognitive Disputation dalam Mereduksi Kecemasan Berbicara di Depan Umum pada Siswa Kelas X Madrasah Aliyah Proyek Univa Medan - Ainun, Nur; Syahputra, Irwan; Manurung, Purbatua (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of group counseling services with cognitive disputation techniques in reducing public speaking anxiety in class X students of Madrasah Aliyah Project UNIVA Medan. The approach used is quantitative research with the Quasi Experimental Design method. The research design applied is Non-equivalent Control Group Design. The study population was 26 students, and the research sample was 10 students selected by purposive sampling technique based on the level of public speaking anxiety in the high category. The research data were obtained from the results of the pretest and posttest using a public speaking anxiety questionnaire instrument. The data analysis technique was carried out using the parametric independent sample t-test, after first fulfilling the prerequisite tests in the form of normality and homogeneity tests. The results showed that the average score of students' public speaking anxiety decreased, from 110.40 (high category) in the pretest to 55.60 (low category) in the posttest. In addition, the t-test value obtained was 2,442, greater than the t-table of 1,895 with a Sig. value. (2-tailed) = 0.040 < 0.05. This means that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that there is a significant influence of group counseling services with cognitive disputation techniques in reducing public speaking anxiety in class X students of Madrasah Aliyah Proyek UNIVA Medan.